2021
DOI: 10.1088/1755-1315/794/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clash detection and quantity take-off using BIM for warehouse construction

Abstract: Lack of integration in the design of a construction project planning, often resulting in clashes between elements. The purpose of this study was to analyze the number and causes of clashes between structural design, precast design, and MEP design for warehousing projects. Then the quantity take-off analysis will be carried out after resolving the clashes. In this study, BIM-based software was used namely Revit® 2020 and Navisworks® Manage 2020. The results of this study found that the number of clashes for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Elyano and Yuliastuti corroborated this in their case study where they found design errors causing 52.36% of the detected clashes which were mostly between structural vs MEP components [4]. Design inconsistency caused 39.13% and design discrepancy caused 8.51% of detected clashes, and these clashes were mostly between structural, MEP, and precast components [4]. This work will address the most prominent causes of clashes identified by contemporary literature while discussing potential clash avoidance strategies.…”
Section: Identifying Causes Of Clashessupporting
confidence: 55%
See 2 more Smart Citations
“…Elyano and Yuliastuti corroborated this in their case study where they found design errors causing 52.36% of the detected clashes which were mostly between structural vs MEP components [4]. Design inconsistency caused 39.13% and design discrepancy caused 8.51% of detected clashes, and these clashes were mostly between structural, MEP, and precast components [4]. This work will address the most prominent causes of clashes identified by contemporary literature while discussing potential clash avoidance strategies.…”
Section: Identifying Causes Of Clashessupporting
confidence: 55%
“…Mehrbod et al specified design discrepancy, design error, and missing items as the causes of design coordination issues [3], design error being the most frequent cause in the study. Elyano and Yuliastuti corroborated this in their case study where they found design errors causing 52.36% of the detected clashes which were mostly between structural vs MEP components [4]. Design inconsistency caused 39.13% and design discrepancy caused 8.51% of detected clashes, and these clashes were mostly between structural, MEP, and precast components [4].…”
Section: Identifying Causes Of Clashessupporting
confidence: 54%
See 1 more Smart Citation
“…However, BIM has been implemented in the infrastructure sector. It offers similar benefits to construction projects regarding project visualization (Vitásek & Zak, 2018;Xing et al, 2020), clash detection (Elyano & Yuliastuti, 2021;Xing et al, 2020), traffic analysis (Castañeda et al, 2021), road e-ISSN: 2723-6692 🕮 p-ISSN: 2723-6595 & pavement design (Tang et al, 2020), existing road analysis (Vignali et al, 2021), quantity takeoff (Chen et al, 2022;Nguyen et al, 2022;Taghaddos et al, 2019), cost estimating (Vitásek & Zak, 2018), and information management (Lin et al, 2020). Over the last two years, there has been significant growth in BIM adoption for transportation infrastructure projects, and this trend is projected to continue.…”
Section: Introductionmentioning
confidence: 99%